Advances in human factors in energy : oil, gas, nuclear and electric power industries : proceedings of the AHFE 2016 International Conference on Human Factors in Energy: Oil, Gas, Nuclear and Electric Power Industries, July 27-31, 2016, Walt Disney World®, Florida, USA /: oil, gas, nuclear and electric power industries : proceedings of the AHFE 2016 International Conference on Human Factors in Energy: Oil, Gas, Nuclear and Electric Power Industries, July 27-31, 2016, Walt Disney World®, Florida, USA. ([2016]) - Unknown
No abstract available